1980
DOI: 10.1128/iai.30.2.607-611.1980
|View full text |Cite
|
Sign up to set email alerts
|

PLC/PRF/5 (Alexander) hepatoma cell line: further characterization and studies of infectivity

Abstract: The Alexander hepatoma cell line, PLC/PRF/5, was studied for evidence of hepatitis B virus markers and alpha-fetoprotein. Only hepatitis B surface antigen and alpha-fetoprotein were detected. Induction experiments with 5-iodo-2'-deoxyuridine and inoculation of chimpanzees with whole cells or tissue culture fluid did not reveal evidence of synthesis of additional hepatitis B virus markers or of production of infectious virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In this research, PLC/PRF/5 human hepatocellular carcinoma cell line was used to investigate the anticancer effects of the standard compounds and extracts. The cell line is a well-characterized hepatocellular carcinoma containing hotspot p53 mutation at R249, which is a unique hotspot codon of liver cancer [ 6 , 36 ]. Though previous studies have reported the effect of hesperidin or limonin on HepG2 cells, liver cancer cell lines with wild-type p53 gene [ 16 , 17 ], this is the first study to report the effect of hesperidin, limonin, combination, and the ethanolic extract of the lime peel on liver cancer cells with hotspot mutated p53.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, PLC/PRF/5 human hepatocellular carcinoma cell line was used to investigate the anticancer effects of the standard compounds and extracts. The cell line is a well-characterized hepatocellular carcinoma containing hotspot p53 mutation at R249, which is a unique hotspot codon of liver cancer [ 6 , 36 ]. Though previous studies have reported the effect of hesperidin or limonin on HepG2 cells, liver cancer cell lines with wild-type p53 gene [ 16 , 17 ], this is the first study to report the effect of hesperidin, limonin, combination, and the ethanolic extract of the lime peel on liver cancer cells with hotspot mutated p53.…”
Section: Discussionmentioning
confidence: 99%
“…It was sourced from a 24 years Shangaan male with HCC from Mozambique (Figure 3A). This cell line continuously produces the HBsAg, however there was no expression for other markers of HBV synthesis [38]. Some oncogenes like c-Myc, c-abl, c-ha-ras c-fes, c-fms, and c-sis oncogenes are indicated in the cell line along with HBsAg.…”
Section: Plc/prf/5(alexander)mentioning
confidence: 96%